UJI AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BATANG SEKILANG (Embeliaborneensis Scheff) TERHADAP BAKTERI Propionibacterium acnes dan Staphylococcus epidermidis - Ari Saptowo; Risa Supriningrum; Supomo supomo (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2022)
Plants as medicinal ingredients have potential as antimicrobials and antioxidants, with various molecules that can protect the human body from pathogens and cellular oxidation. This is closely related to the secondary metabolitescontained in these plants. Currently there are several bacteria that are resistant to antibiotics, therefore it is necessary to find an alternative to overcome this resistance by conducting research on medicinal plants. Sekilang (Embeliaborneensis) is a plant that is used by the Dayak tribe in Kalimantan as an ingredient for catching fish, repelling leeches and hair care and does not rule out having medicinal properties. So it is necessary to do research on these plants, especially the bark. The purpose of this study was to determine the antibacterial activity of sekilang bark extract against Propionibacterium acnes and Staphylococcus epidermidis bacteria. Extraction of the active substance was carried out by maceration with ethanol solvent and antibacterial activity test using the disc diffusion method. The results of phytochemicalscreening showed that the bark extract of sekilang contains saponins, flavonoids, alkaloids and tannins. The results of the antibacterial activity test against Propionibacterium acne at a concentration of 2.5%; 5% ; 10% and 20% are 6.5 mm, respectively; 8.36 mm ; 7.5mm; 7.33mm. Antibacterial activity against Staphyllococus epidermidis at a concentration of 2.5%; 5% ; 10% and 20% are 7.0 mm, respectively; 7.7mm; 6.33mm; 7.8mm. It was concluded, that the bark extract of sekilang have antibacterial activity against Propionibacterium acne and Staphyllococus epidermidis with moderate category. The positive control used was clindamycin and the negative control was Dimethyl sulfoxy.